License to Share: The Ugly Side of Creative Capitalism and the Irony of the Commons - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2007)
In the real world, capitalism has largely influenced the development of the copyright regime as it exists today. However, the emergence of a cyberspace society requires us to revisit communitarian values in the light of the unique features of virtual interaction and the changing expectations and attitudes towards the control and use of creative works. As copyright legal and technological protections continue to expand, private initiatives through creative licensing provide some relief to their restrictions.